2012
DOI: 10.1002/jrs.4088
|View full text |Cite
|
Sign up to set email alerts
|

In situ Raman monitoring of materials under irradiation: study of uranium dioxide alteration by water radiolysis

Abstract: In situ Raman scattering studies allow following real-time evolutions of volume or surface structures under extreme conditions. In nuclear materials sciences, ion irradiation-induced atomic organization modification and water radiolysis are of a major interest. In order to better understand these phenomena, we have developed an in situ versatile portable Raman spectroscopy system coupled with a cyclotron accelerator, allowing monitoring of a solid/liquid interface under irradiation and thus giving access to ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
4
40
1
Order By: Relevance
“…The Raman spectra contains a v 1 uranyl band located at 831 cm −1 and a secondary v 1 (O=O) stretching mode at 870 cm −1 [95]. Both studtite and the dehydrated form (metastudtite [UO 2 (O 2 )(H 2 O) 2 ]) have been identified as a secondary alteration phase formed due to the alpha radiolysis of water using Raman spectroscopy as the main surface characterization technique [76,77,96,97]. …”
Section: Chemical and Structural Elucidation Of Uranium Solid-state Cmentioning
confidence: 99%
“…The Raman spectra contains a v 1 uranyl band located at 831 cm −1 and a secondary v 1 (O=O) stretching mode at 870 cm −1 [95]. Both studtite and the dehydrated form (metastudtite [UO 2 (O 2 )(H 2 O) 2 ]) have been identified as a secondary alteration phase formed due to the alpha radiolysis of water using Raman spectroscopy as the main surface characterization technique [76,77,96,97]. …”
Section: Chemical and Structural Elucidation Of Uranium Solid-state Cmentioning
confidence: 99%
“…In situ Raman monitoring of He 21 irradiation induced damage in a UO 2 ceramic G. Guimbretière, 1,a) L. Desgranges, 2,b) A. Canizarès, 1 R. Caraballo, 3 F. Duval, 1 N. Raimboux, 1 R. Omn ee, 1 M. R. Ammar, 1 C. J egou, 3 The in situ Raman probing of a UO 2 ceramic in [Ar/H 2 , 95/5] gas atmosphere followed by exposure to He 2þ ionic irradiation coming from a cyclotron accelerator was implemented. It was observed that the growth of Raman defect bands exhibits a unique kinetic nicely modelized by a simple direct impact model, and with an annealing rate constant of 5.6 Â 10 À4 6 4 Â 10 À5 s À1 for an ionic flow of 50 nA and an ions-beam induced sample heating of 170 6 10 C. Also, it was observed that the Ar plasma induced by the ions-beam is a sensitive probe of the presence of the ions-beam.…”
mentioning
confidence: 99%
“…2 For this purpose, at CEMHTI lab, we have developed a unique setup coupling of a cyclotron beam with a Raman spectrometer, allowing in situ probing of the solid/fluid interface under irradiation. 3 Such instrument was previously used for identification and observation of the growth of an alteration layer at the UO 2 /H 2 O interface. 3,4 Besides, we have recently shown that Raman spectroscopy is also a useful tool for the study of damage in the solid UO 2 : We observed from post-mortem Raman measurements that He 2þ irradiation induced the appearance of Raman defect-bands (called U 1 , U 2 , and U 3 ) that grow up with the energy deposited by the ions-beam.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31][32][33][34] At JANNUS-Saclay, a Raman probe is now permanently installed in the triple beam chamber and IBIL has been tested. Both devices are described in this section.…”
Section: In Situ Damage Characterizationmentioning
confidence: 99%